Metapopulation models of pandemic risk and control - Singer, BJ (2021)
A pandemic is a global outbreak of an infectious disease, which can increase rates of death and disability worldwide, and impact economies and civilisations more generally. Ascertaining the risk of large pandemics with high mortality is challenging, due to their rarity. We can understand pandemics better by using the methods of theoretical epidemiology. In this thesis, I explore what one of these methods—metapopulation models—can tell us about pandemic risk and control. Metapopulation models can represent the spatial spread of pathogens, and thereby capture the global nature of pandemics.